Personal branding on Instagram: an examination of Iranian professional athletes. Issue 5 (9th August 2021) - Sharifzadeh, Zahra; Brison, Natasha T.; Bennett, Gregg
Abstract : Purpose: This study investigates the personal branding strategies utilized by Iranian professional athletes. It also examines the challenges these athletes face in attempting to create a personal brand. For example, unlike their global counterparts, Iranian athletes' access to social media is limited to only Instagram, due to a ban in Iran on the use of Facebook and Twitter. This specific situation provides unique opportunities and interactions in the personal branding process. Design/methodology/approach: Utilizing a criterion purposive sample of Iranian professional athletes, the authors conducted in-depth, semi-structured interviews to understand the branding strategies and challenges of these athletes. Findings: Two categories (branding strategies and cultural/societal challenges), along with Six themes emerged. The categories were derived based on the literature review and the subsequent research questions. Originality/value: This paper provides valuable information on challenges and opportunities for athletes' personal branding from international perspectives. Also, the results of the study broaden our understanding of how athletes' personal branding can function in different countries and contexts. Findings will provide governing bodies and sport marketers have a better understanding of athletes' social media usage.